Pirfenidone for primary Sjögren’s syndrome-related fibrotic interstitial pneumonia - Enomoto, Yasunori; Nakamura, Yutaro; Colby, Thomas V.; Inui, Naoki; Suda, Takafumi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Primary Sjögren’s syndrome-related interstitial pneumonia (pSS-IP) is occasionally progressive even with immunosuppressive therapy and new treatment options are warranted. A 42-year-old woman was diagnosed with pSS-IP with pathological usual interstitial pneumonia pattern. Although her forced vital capacity (FVC) had temporarily improved after prednisolone therapy, it deteriorated during the prednisolone tapering off period. Therefore, pirfenidone was added in conjunction with prednisolone. During the 12-month treatment period, her FVC was almost stable. A 62-year-old man, a current heavy smoker, was diagnosed with pSS-IP. Chest computed tomography showed bilateral honeycombing with ground-glass attenuation on a background of emphysema. He gradually developed dyspnea on exertion and his FVC deteriorated. Hence, pirfenidone was administered as a monotherapy. Six months later, his FVC and exercise tolerance had significantly improved. Pirfenidone might have a role for the treatment of pSS-IP.